2018
DOI: 10.1007/s00453-018-0464-z
|View full text |Cite
|
Sign up to set email alerts
|

Space-Efficient Biconnected Components and Recognition of Outerplanar Graphs

Abstract: We present space-efficient algorithms for computing cut vertices in a given graph with n vertices and m edges in linear time using O(n + min{m, n log log n}) bits. With the same time and using O(n+m) bits, we can compute the biconnected components of a graph. We use this result to show an algorithm for the recognition of (maximal) outerplanar graphs in O(n log log n) time using O(n) bits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 27 publications
(16 reference statements)
1
32
0
Order By: Relevance
“…Space bounds of the form O(n log(m/n)) for the same problems were mentioned by Chakraborty et al [5]. Essentially re-inventing an algorithm of Gabow [10] and combining it with machinery from [9] and with new ideas, Kammer et al [15] also demonstrated how to compute the cut vertices in O(n + m) time with O(n log log n) bits. Finally, decomposing the input graph into subtrees and processing the subtrees one by one, Chakraborty et al [5] were able to solve the BCC problem and compute the cut vertices in O(m log n log log n) time with O(n) bits.…”
Section: Introduction and Related Workmentioning
confidence: 82%
See 4 more Smart Citations
“…Space bounds of the form O(n log(m/n)) for the same problems were mentioned by Chakraborty et al [5]. Essentially re-inventing an algorithm of Gabow [10] and combining it with machinery from [9] and with new ideas, Kammer et al [15] also demonstrated how to compute the cut vertices in O(n + m) time with O(n log log n) bits. Finally, decomposing the input graph into subtrees and processing the subtrees one by one, Chakraborty et al [5] were able to solve the BCC problem and compute the cut vertices in O(m log n log log n) time with O(n) bits.…”
Section: Introduction and Related Workmentioning
confidence: 82%
“…In this subsection we will see that closely related algorithms can be used to compute the cut vertices, the bridges and the biconnected and 2-edge-connected components of an undirected graph. Our algorithms are similar to those of [3,5,15], but whereas the earlier authors indicated the space bounds only as O(n + m) or O(n log(m/n)) bits, we will strive to obtain small constant factors and indicate these explicitly.…”
Section: Biconnected and 2-edge-connected Componentsmentioning
confidence: 93%
See 3 more Smart Citations